Assessment of different approaches to implementation of the IPPC Directive and their impacts on competitiveness: some evidence from the steel and glass industry. Study on behalf of the European Commission, DG Environment - Tilmann Rave; Ursula Triebswetter (ifo Institut für Wirtschaftsforschung an der Universität München, 2007)
This study aims at assessing the impacts of different approaches to IPPC implementation on competitiveness of companies in two industrial sectors (electric steelmaking and domestic glass production). As the provisions of the IPPC Directive allow a certain flexibility for Member States to set permit conditions and to apply the concept of Best Available Techniques (BAT), the implementation of the IPPC Directive is likely to differ across the EU. Furthermore, the Directive does not contain any detailed requirements concerning later stages of the regulatory cycle” like monitoring and inspections which also may influence competitiveness. Therefore, while differences in implementation of the IPPC Directive across the EU might be justified due to specific circumstances, this may result in distortion of competition and an influence on the competitiveness of certain production sites and industry sectors within and across Member States. There may also be competitiveness impacts relative to non-EU competitors.
Keywords: C12; Q53; Q58; 330; Umweltschutz; Umweltbelastung; Gesetzgebung; Umweltrecht; Kontrolle; Wettbewerb; Umweltpolitik; Glasindustrie; Stahlindustrie; Wissenschaftliche Methode; Umweltbelastung; EU-Umweltrecht; Internationaler Wettbewerb; Stahlindustrie; Glasindustrie; EU-Staaten